Blastocystis spp. infection in children and teenagers: prevalence in four rural communities, Bolívar State, Venezuela (Revista Venezolana de Salud Pública, 2021)
The infection by Blastocystis spp. is denominate Blastocystosis and it is the most common intestinal parasitosis in Venezuela today. To determine the prevalence of Blastocystis spp. in children from the rural communities “Angosturita”, “Angostura Cruce de Bolívar” (ACB), “Los Báez” and “Palmarito” of the municipality “Angostura del Orinoco” of the Bolívar state, between March 2016 and May 2018, a cross sectional study was realized. 162 children were evaluated (30, 26, 82 and 74, respectively), where the most studied group was that of schoolchildren with 54.9% (n = 89). 93 female children/teenagers (57.4%) and 69 male children/teenagers (42.6%) were included. The general prevalence of intestinal parasites was 77.8%. Fourteen taxa of enteroparasites (4 chromists, 6 protozoa and 4 helminths) and one myxozoa (Myxobolus spp.) were identified. Blastocystis spp. it was the one with the highest prevalence with 62.3%. School-age children were more affected by Blastocystis spp. (71.9%), being the difference statistically significant (χ2 (Yates correction) = 10.36 d.f. = 3 p 0.05). 67.3% of children/teenagers with Blastocystis spp. he was poliparasitized. The most associated agent with Blastocystis spp. was Entamoeba. coli with 54.4%. In conclusion, we determined a high prevalence of Blastocystis spp. in children/teenagers from four rural communities in the municipality “Angostura del Orinoco” in Bolívar state, being schoolchildren the most affected and without differences regarding gender.
Keywords: Blastocystis spp; epidemiology; teenagers; children; rural community